Breast cancer risk and lifetime occupational history: employment in professional and managerial occupations. Issue 1 (January 1998) - Petralia, S A; Vena, J E; Freudenheim, J L; Marshall, J R; Michalek, A; Brasure, J; Swanson, M; Graham, S
Abstract : OBJECTIVE: In this case-control study, occupational histories were used to assess the relation between risk of breast cancer and employment in professional and managerial occupations while adjusting for reproductive and other risk factors. METHODS: Incident, primary, female cases of breast cancer diagnosed between 1986 and 1991, and randomly selected controls were interviewed to obtain detailed medical, reproductive, and occupational histories. Mantel-Haenszel crude odds ratios (OR) and 95% confidence intervals (95% CIs) were used to estimate risk of breast cancer related to the job of longest duration. Unconditional logistic regression was used to estimate crude and adjusted ORs and 95% CIs associated with having ever been employed and duration of employment in a professional or managerial occupation. RESULTS: A non-significant threefold increase in risk was found among premenopausal women whose major job was in the occupational category of precision production, craft, and repair (95% CI 0.90 to 20.35). No increase in risk was found for premenopausal women whose major job was a managerial or professional occupation. However, an inverse relation between risk of premenopausal breast cancer and having ever held a professional or managerial job was observed (OR 0.53, 95% CI 0.34 to 0.82). This relation was strongest for women who worked one to 10 years (OR 0.47, 95% CI 0.29 to 0.77). Postmenopausal breast cancer was not related to professional and managerial employment. CONCLUSIONS: In this population, employment in professional and managerial occupations is not associated with postmenopausal risk of breast cancer, but seems to be related to a reduction in risk of premenopausal breast cancer. Methodological limitations of this study including response rates are discussed.